Activities, transcript levels, and subcellular localizations of sucrose phosphate synthase, sucrose synthase, and neutral invertase and change in sucrose content during fruit development in pineapple (Ananas comosus). Issue 5 (3rd September 2019) - Zhang, X.M.; Liu, S.H.; Du, L.Q.; Yao, Y.L.; Wu, J.Y.
ABSTRACT: Sucrose phosphate synthase (SPS), sucrose synthase (SuSy), and neutral invertase (NI) are the three enzymes involved in sucrose synthesis and cleavage in higher plants. However, the key enzyme(s) responsible for sucrose accumulation is/are inconsistent in different species or different varieties of the same species. The regulation of sucrose accumulation in Tainung 11 pineapple ( Ananas comosus ) has not been reported to date. In this study, the sucrose content and the activities and patterns of transcript levels of the three enzymes were analysed in the flesh of Tainung 11 pineapple during fruit development. From 20 to 100 days after anthesis (DAA), the activities and transcript levels of SPS and SuSy gradually increased. Meanwhile, the NI activity and transcript level dramatically decreased from 40 to 100 DAA. The sucrose accumulation increased from 20 to 100 DAA. These findings suggested that AcSPS, SPS, AcSuSy, and SuSy were responsible for sucrose synthesis, but AcNI and NI were responsible for sucrose cleavage in Tainung 11 pineapple. The subcellular localisations of AcSPS, AcSuSy, and AcNI were first identified. Both AcSPS and AcSuSy were found in the cytosol, while AcNI was localised in the vacuole.